High Temperature Assessment of K-Tl Binary Liquid Alloy (Journal of Nepal Physical Society, 2020)
Theoretical study of thermodynamic properties of binary liquid Potassium-Thallium alloy at temperatures 798 K, 1000 K, 1200 K and 1400 K have been analyzed as a function of concentration by considering temperature dependent exponential interaction parameters in the framework of R-K polynomials. The viscosity and surface tension of the alloy have been studied by BBK model and improved derivation of Butler equation respectively. The study provides the information of moderately interacting as well as segregating nature at the low concentration of Thallium and ordering nature at high concentration of Thallium and the viscosity and surface tension of the alloy decrease with increase in temperature.